Analisis Strategi Pengembangan Bisnis dengan Metode Business Model Canvas (BMC) dan Quantitative Strategic Planning Matrik (QSPM) - Rina Kurniawati; Hilmi Aulawi; Sabila Rismawati (Institut Teknologi Garut, 2022)
The benefit of this research is to help companies deal with problems that occur, namely the decline in product sales caused by the Covid-19 pandemic and which still have an impact on the new normal era. The business development strategy utilizes mapping of the company's business concept using the Business Model Canvas (BMC) method which consists of nine block elements, after which an analysis phase is carried out to determine internal and external factors that influence the company, using the Internal Factor Assessment Strategy (IFAS) matrix of strength factors with the highest value must be maintained while for the company's weakness factors it must be able to handle so that it does not become an obstacle for the company, and for the External Factor Assessment Strategy (EFAS) matrix the highest opportunity factor can be utilized by the company for business development in a better direction, while for threat factors the company should be able to handle it. After that determining the company's position using the internal-external (IE) matrix by using this matrix it is known that the company's position is located between one of the cells. Furthermore, designing a strategy with a SWOT matrix, so that it will produce four elements of the strategy resulting from the identification of strengths, weaknesses, opportunities and threats. Then the final stage is the decision-making stage using the Quantitative Strategic Planning Matrix (QSPM). Based on the results of data processing, the strategy chosen was the penetration strategy because the results of data processing showed the highest Total Attractiveness Scores (TAS).